Amplification and expression of human alpha-globin genes in Chinese hamster ovary cells. - Lau, Y F (1984)
We studied the effects of gene amplification on human globin gene expression in Chinese hamster ovary cells. The normal human alpha-globin gene (N alpha 2) and a hybrid gene (M alpha G) containing the 5' promoter-regulator region of the mouse metallothionein gene and the human structural alpha 2-globin gene were linked to a modular SV2-cDNA dihydrofolate reductase (DHFR) gene. The recombinant DNA molecules were introduced into Chinese hamster ovary cells by calcium phosphate precipitation. After initial selection to retain the DHFR and linked sequences, the cells were cultured in increasing concentrations of methotrexate up to 0.2 mM. Southern blot analysis of total cellular DNA showed an approximately 500- to 1,000-fold increase in the number of copies of DHFR and human alpha-globin genes. The transcription of the alpha-globin and DHFR genes increased as their copy number within the cells increased. The transcription of the amplified hybrid M alpha G gene was also inducible with cadmium treatments. Both mature mRNA and "read-through" transcripts were observed. DHFR constituted approximately 10% of pulse-labeled cellular proteins in these cells, but no human alpha-globin was detected. In vitro translation of polyadenylated RNA from these cells showed that alpha-globin mRNA transcribed from the amplified alpha-globin genes was functional and directed alpha-globin chain synthesis. In situ hybridization of 3H-labeled alpha-globin and DHFR DNA probes in chromosome preparations from the two cell lines indicated that both genes were coamplified in the same chromosomal locations in each cell type. These results indicate that gene amplification enhances human globin gene expression in cultured Chinese hamster ovary cells.